Causes of Divorce in Bosnia and Herzegovina Society - Karolina Tadić-Lesko (Društvene i Humanističke Studije)
In divorce proceedings, violence, manipulation, denial of child support contributions and violation of divorce agreements, stress due to financial worries and uncertainty about the future are increasingly visible. The aim of this paper is to investigate the causes of divorce in Bosnian and Herzegovina society and to analyze the perspectives for preventing its consequences. The paper used the method of content analysis (scientific and professional literature and other documentation and data collected from B&H websites on the experiences of experts working in divorce proceedings, with an emphasis on the Federation of B&H, for the period 2018-2024). The results of the research showed that the most com-mon causes leading to divorce are: adultery, addictions, financial difficulties, violence, mismatch of temperaments, unrealistic expectations and separate lives, while the possibilities of experts in working to prevent the consequences of divorce are visible through work in marriage counseling centers, amendments to social and criminal legislation and prevention. It is necessary to undertake preventive interventions in social welfare with the aim of premarital counseling, preventing the occurrence of high-conflict divorces de lege ferenda (by conducting informative, preparatory counseling conversations with spouses as a precursor to the pre-divorce mediation process and the court divorce process), to provide professional support by strengthening parental competencies (responsibilities and duties after divorce), and to effectively implement measures of protection against violence.